Methodology for Assessing the Vulnerability of Participants in Regional Food Markets - Alekseev, Aleksander O.; Kovalenko, Aleksandr I.; Svetlakov, Andrei G. (Economy of Regions, 2021)
The vulnerability of regional food markets is difficult to study due to the lack of a unified approach to analysing the weaknesses of agricultural enterprises, which is necessary for investigating their response to external and internal changes. The study aims to solve this problem by developing an adaptable method for assessing the vulnerability of organisations that produce, process and sell agricultural products in regional food markets. For this purpose, we applied hierarchical mechanisms of integrated assessment for combining various indicators of agricultural enterprises into a single vulnerability score. The present research examines the alcohol market: while this particular sector is represented by a small number of producers, these organisations are usually the largest taxpayers in the agri-food industry, especially in areas of risky farming. As an example, we show how the vulnerability of Permalko JSC (a large producer of alcoholic beverages) has changed because of the COVID-19 pandemic. This company not only satisfies the needs of Perm oblast’s market, but also exports its production to many Russian regions, as well as to near and far abroad. As a result, we propose a new methodology, represented by a set of mathematical formulas, and define its variables. This versatile approach to vulnerability assessment can be adapted for any agri-food enterprise by specifying the parameters. The model is implemented in the dekon software package, which is a web application. The cloud service will provide unified access to all agricultural enterprises.